2020
DOI: 10.1186/s13223-020-00444-y
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of anaphylaxis to Indian jujube (Ziziphus Mauritiana Lam)

Abstract: Background: Indian jujube (Ziziphus Mauritiana Lam) is a sweet fruit from a tree native to tropical and subtropical regions of Asia and India. A few case reports have implicated Indian jujube to cause latex-fruit syndrome. We present the first case of an anaphylactic reaction to this fruit in a patient with no latex allergy. Case presentation: A 55-year-old male was referred to the Outpatient Allergy Clinic at Queen's University for evaluation of anaphylaxis caused by ingestion of Indian jujube. He presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…There was previously a report on jujube allergy caused by latex-fruit syndrome 4 , and a recent report of IgE-mediated anaphylaxis without latex sensitization in an adult 5 ; however, our study is the first to report an anaphylaxis induced by jujube via IgE-mediated immune response in a child. In addition, unlike previous reports that were about allergy symptoms by Indian jujube (Z. mauritiana), this study is the first to report about Chinese jujube (Z. jujuba Mill).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…There was previously a report on jujube allergy caused by latex-fruit syndrome 4 , and a recent report of IgE-mediated anaphylaxis without latex sensitization in an adult 5 ; however, our study is the first to report an anaphylaxis induced by jujube via IgE-mediated immune response in a child. In addition, unlike previous reports that were about allergy symptoms by Indian jujube (Z. mauritiana), this study is the first to report about Chinese jujube (Z. jujuba Mill).…”
Section: Discussioncontrasting
confidence: 60%
“…4 7 However, although the patient in our study showed sensitization to kiwi and pine nuts from the skin prick test and clinically, the result from the skin prick test to latex was negative, this implied a chance of cross reaction of symptom-inducing Chinese date with components of kiwi or pine nuts. Particularly in the case of an adult patient in Canada 5 , who often had Indian jujube as dessert but did not take it at all after moving to Canada, symptoms appeared after reintake after a certain period of time. The skin prick test for jujube was positive, which suggested induction of allergy symptom by sensitization to jujube itself without sensitization to other antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation